Forensic chemistry - Bell, Suzanne (Boca Raton : CRC Press, 2022)
"Forensic Chemistry, Third Edition introduces students to the principal areas of the field from the perspective of analytical chemistry. The book provides a working foundational knowledge base for basic chemistry, introducing chemical concepts and practices from a forensic perspective (including multivariate statistics, quality assurance/quality control, and protocols used in working forensic laboratories). The book distinguishes forensic chemistry from other types of analytical chemistry by the legal context in which the work is done, the types of samples and matrices, the variety of sample types encountered, and the extensive use of instrumentation. Topics covered in the various chapters offer students insight into the legal context in which forensic chemistry is conducted, introducing students to the variety of types of samples and matrices, and extensive use of instrumentation they will likely encounter in the lab and future professions"--
Includes bibliographical references and index.
Keywords: Chemistry, Forensic; Analytical chemistry